Features of Organization of Accounting in Service Enterprises (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the features of accounting organization in service enterprises, the theoretical basis, analysis and organization of accounting of income and expenses, directions for organization of accounting accounting based on international standards, problems of organization of accounting accounting in service enterprises and their improvement ways are given.